Ring chromosome 14: a distinct clinical entity. Issue 4 (August 1981) - Schmidt, R; Eviatar, L; Nitowsky, H M; Wong, M; Miranda, S
Abstract : An infant girl with ring chromosome 14 is presented. The findings in this patient and in six previously reported cases of a ring 14 suggest that a characteristic clinical syndrome is associated with this chromosome aberration. The major features of the ring chromosome 14 syndrome include mental retardation, a disorder of skin pigmentation, seizures, and dysmorphic features, including flat occiput, epicanthal folds, downward slanting eyes, flat nasal bridge, upturned nostrils, short neck, and large low set ears.